Oral lipectomy: mediate surgical complication report (Research, Society and Development, 2020)
The buccal fat pad described as a fatty tissue located on the face and its removal is known as buccal lipectomy or bichectomy, and may be indicated as aesthetic and functional purpose. A 33-year-old female patient sought treatment because of bilateral morsicatio. Oral lipectomy surgery was performed and after three hours of the procedure, one patient reported disproportionate and unilateral facial edema, with presence of mild and late pain, having shown periorbital hematoma training and right eye bruising. One patient required further intervention to explore a wound requiring hematoma drainage, followed by pressure maneuvers and cauterization with a monopolar electric scalpel. In view of the stabilization of the bleeding, the patient was instructed to use antibiotics, as well as control pain with analgesics and cryotherapy, being monitored daily until the return of edema was evident. The hematoma was recorded at 30 days without functional and aesthetic impairment. Oral lipectomy surgery should be performed by a qualified professional with experience in an outpatient and hospital environment, with the ability to intervene early on possible complications, minimizing the possibility of progression to more significant complications.